Preferential Tax Regimes. Offshore Corporate Profits in the Asia-Pacific Region - Plaza Reveco, Rafael Mauricio (Revista Tribuna Internacional, 2020)
The enquiry aims at contributing to international trade and foreign investment in the Asia-Pacific region through using preferential tax treatments on offshore trading companies’ corporate profits. The methodology compares tax jurisdictions from Asia and OECD countries applicable to case studies. Firstly, it addresses incorporation of limited liability corporations, investment and foreign currency frameworks as well as taxation on corporate profits in Hong Kong. Secondly, it delves into offshore companies incorporated in Delaware, its documentation of company rights ownership and identity of shareholders´ confidentiality rules. Finally, it examines two cases studies involving companies with limited liability and the turnaround of imported products destined for sale in mainland China´s market. The paper advances the incorporation of offshore limited liability companies as part of a tax planning aimed at furthering export businesses earning corporate profits in the Chinese market and/or acquiring capital goods not intended for offshore jurisdictions.